Implementation of the Character Education Curriculum in Cultivating Students' Morality at Raudhatul Athfal At Taufiq Salam Labuhanbatu Utara - Aziz, Mursal; Napitupulu, Dedi Sahputra; Lestari, Dari Ayu (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to analyze the implementation of the character education curriculum at Raudhatul Athfal At Taufiq Salam Labuhanbatu Utara and its effectiveness in cultivating students' morality through early childhood education practices. Methodology: This research employed a qualitative descriptive approach. Data were collected through observations, documentation, and interviews with teachers and school administrators. The study focused on how character values were embedded in daily school activities, thematic learning, teacher modeling, and school culture. Supporting literature and relevant documents were also analyzed to validate findings. Main Findings: The findings revealed that character values such as religiosity, honesty, discipline, and social care were effectively instilled through an integrated approach. The main challenges included limited teacher understanding of character-based pedagogy, lack of synergy between school and parents, and inadequate facilities. Nonetheless, the character education practices at Raudhatul Athfal At Taufiq Salam contributed positively to students' moral development. Novelty/Originality of this study: This study contributes to the field of early childhood education by highlighting the contextual implementation of character education within an Islamic preschool setting. It emphasizes the integration of moral values into routine learning, offering insights into best practices and practical challenges faced by educators in rural Indonesian schools.